Pengaruh Self-Efficacy terhadap Kecemasan Berbicara di Depan Umum pada Mahasiswa Akhir Universitas Negeri Padang - Sarfika, Ika; Nio, Suci Rahma (Lembaga Yasin AlSys, 2025)
This study aims to determine whether there is an influence of self-efficacy on public speaking anxiety among final students at Padang State University. Public speaking anxiety is a feeling of fear or anxiety that a person experiences when they have to communicate with other people. This research received 66 final students as respondents, 46 female respondents and 20 male respondents. The technique used to collect subjects was purposive sampling. This research uses quantitative methods where data is collected through distributing questionnaires. Data analysis was carried out using simple regression analysis with a Likert scale. This research found that there is a negative influence between self-efficacy on public speaking anxiety. Based on simple linear regression analysis, the determinant coefficient (R Square) is 0.0691 (69.1%). These findings indicate that the Ha hypothesis is accepted and Ho is rejected.